Analisis Potensi Bahaya Terhadap Program Kerja Departemen Maintenance Di Stasiun Sterilizer Menggunakan Metode Job Safety Analysis (JSA) di PT. X Nagan Raya - Devhani Nainggolan; Jun Musnadi Is; Firman Firdauz Saputra; Wintah Wintah; Rubi Rimonda (PT.Mantaya Idea Batara, 2024)
The Sterilizer Station at PT X Nagan Raya is a company facility that requires regular maintenance by the maintenance department to ensure its smooth operation. This facility has potential hazards that need to be analyzed in detail. This study aims to evaluate each potential hazard associated with the maintenance department's work programs at the Sterilizer Station using the Job Safety Analysis (JSA) method, where these potential hazards will be evaluated for the associated risk levels, namely low risk, medium risk, high risk, and extreme risk. The research approach used is qualitative with a descriptive design. Data was collected from the maintenance department's work program for the July-December 2023 period at the Sterilizer Station through direct observation and interviews using the JSA form. The informants in this study were 6 informants consisting of maintenance employees, maintenance assistants, HSE officers and Assistant Mill Managers. The results of this study state that there are several potential hazards that can occur during the implementation of the maintenance department work program, such as the danger of falling on work equipment, slipping, electric shock, exposed to sparks, exposed to mesingerinda, iron cutters and electric welding machines. Based on the JSA analysis, several risk control measures are suggested, such as the use of appropriate and correct Personal Protective Equipment (PPE), routine maintenance of equipment, monitoring of the work program.